Colorectal endoscopic full-thickness resection using a novel, flat-base over-the-scope clip: a prospective study - Backes, Yara; Kappelle, Wouter F. W.; Berk, Luuk; Koch, Arjun D.; Groen, John N.; de Vos tot Nederveen Cappel, Wouter H.; Schwartz, Matthijs P.; Kerkhof, Marjon; Siersema, Peter D.; Schröder, Roland; Tan, T. G.; Lacle, Miangela M.; Vleggaar, Frank P.; Moons, Leon M. G.; on behalf of the T1 CRC Working Group (Endoscopy, 2017)
Background and study aims We aimed to evaluate the feasibility and safety of a new, flat-based over-the-scope clip (Padlock Clip) for colorectal endoscopic full-thickness resection (eFTR).Patients and methods We prospectively included 26 patients with lesions < 20 mm. Indications for eFTR were re-resection of the scar of a low risk malignant polyp (n = 11), recurrent adenoma in a non-lifting scar (n = 10), non-lifting polyp (n = 4), and an adenoma located in a diverticulum (n = 1). Results Technical success rate and full-thickness resection rate were 100 % (26/26) and 92 % (24/26), respectively. Median procedure time was 43 minutes (IQR 27 – 56). No complications occurred during the procedure; 3 complications (12 %) occurred within 48 hours, of which one was a perforation requiring laparoscopic suturing. Specimen volumes from eFTR of scar tissue where the original polyp had been ≥ 20 mm (n = 13) were smaller compared with those from non-scar resections or scars where the original polyps had been < 20 mm (n = 13) (median 0.8 vs. 1.5 cm3, P = 0.03).Conclusions In this first series of colorectal eFTR using the Padlock Clip, feasibility was demonstrated. It was relatively safe in view of surgery as the alternative treatment, but could still benefit from technical refinement. Future studies should explore for which indication this technique is most suitable.Trial registration: NTR5562 (Dutch Trial Register).